Cinnamon essential oil synergizes with sodium hypochlorite to suppress VBNC formation in Escherichia coli O157:H7 by modulating the temporal expression of arcA/relA-associated stress regulators - Haoqing Zhao; Zongwei Bai; Jingfeng Zhang; Yamei Chen; Huiting Huang; Xiaoxuan Wang; Jiawen Sun; Lei Shi; Xiaoli Xu; Lichao Zhao (Food Microbiology, 2027)

Constructing electronic-ionic bicontinuous networks for high-fidelity bioelectrical monitoring with 24-hour stable interfaces - Guangyuan Xu; Chuantian Ren; Weiguang Wang; Yufeng Wu; Yiqian Zhou; Ming Lei; Jingfeng Zhang; Kai Huang; Hui Wu (Chemical Engineering Journal, 2026)

Electrostatic shielding and metabolic interplay in microbial defense: Unraveling the dual stress responses of nitrification-anammox systems to per/polyfluoroalkyl substances and quaternary ammonium compounds - Hanyi Wang; Jingfeng Gao; Zhiqi Wang; Yuxuan Wang; Yi Guo; Hongxin Xu (Journal of Hazardous Materials, 2026)

Asynchronous alterations in bacterial composition and function increased functional redundancy related to greenhouse gas emissions following coastal habitat transitions - Jichen Qiu; Junhong Bai; Di Wang; Yuhao Xu; Yue Liu; Yujia Zhai; Jingfeng Wang; Changhong Xiao; Langying Long; Huihua Lyu; Mengwei Chu (Marine Pollution Bulletin, 2026)

Restraining grain growth and constructing defects in olivine-type silicate as high-performance cathode for rechargeable magnesium batteries - Jie Xu; Minjie Zhang; Rui Pu; Guangsheng Huang; Jingchao Zhang; Jianrong Zeng; Yanan Chen; Jingfeng Wang; Jili Yue; Fusheng Pan (Chemical Engineering Journal, 2026)

Turncoat? Native Nitrogen‐Fixing Legumes Facilitate Plant Invasion via Soil Microbes and Nitrogen Transfer - Zhenwei Xu; Warwick J. Allen; Linwei Wu; Menglong Liu; Yi Hu; Jingfeng Wang; Mingyan Li; Xiao Guo; Weihua Guo (Global Change Biology, 2026)
Nitrogen deposition often promotes plant invasions and can arise from multiple sources. However, it remains unclear whether native legumes facilitate invasive plants directly through biotic nitrogen transfer or indirectly via soil microbial mediation. It is also unknown how exogenous nitrogen addition influences these facilitative effects. To address these questions, we combined evidence from a greenhouse experiment and global meta‐analysis. The greenhouse experiment tested the effects of neighboring plants (a native nitrogen‐fixing legume Albizia julibrissin ; a native non‐nitrogen‐fixing legume Styphnolobium japonicum ; or a conspecific) on the growth of invasive Rhus typhina and its native congener R. chinensis . Within‐pot membrane treatments were used to obstruct microbial and nitrogen movement between focal and neighboring plants, with and without added nitrogen. The total biomass of invasive R. typhina increased when grown with the nitrogen‐fixing legume compared with conspecific neighbors, but not when grown with the non‐nitrogen‐fixing legume. Positive effects of the nitrogen‐fixing legume on R. typhina were suppressed when nitrogen transfer or soil microbial movement was obstructed by membranes. Exogenous nitrogen addition did not alter the growth of invasive R. typhina or its interactions with legumes. The biomass of native R. chinensis did not differ among neighboring plant treatments, indicating that facilitation by legumes favored the invasive species. The global meta‐analysis of 268 effect sizes from 46 studies of the effects of legumes on neighboring plants also revealed that native legumes enhanced invasive plants' performance. Together, our findings recognize nitrogen‐fixing legumes as overlooked facilitators of plant invasion, operating through both nutrient and microbial mediated pathways. These findings highlight a paradox in which native species can act as “turncoats,” accelerating invasion and reshaping plant communities under global change.

Habitat changes induced by converting coastal aquaculture to wetlands enhance taxonomic diversity and cross-species interaction strength of macro- and meiobenthos - Jichen Qiu; Wenjing Cao; Zhaohan Zhang; Junhong Bai; Liangxing Cao; Yuhao Xu; Jiajie Mei; Yaqi Wang; Yue Liu; Jingfeng Wang; Yanan Zhang (Aquaculture, 2026)

Synchronous achievement of sludge reutilization, carbon emission reduction and N2O mitigation through partial denitrification driven by periodate-pretreated sludge fermentation - Hongxin Xu; Jingfeng Gao; Hanyi Wang; Tianyi Lu; Ke Zhang (Chemical Engineering Journal, 2026)

Pulmonary sclerosing pneumocytoma with lymph node metastasis and high 18FDG uptake in PET/CT: a rare case report and literature review - Jingfeng Xu; Yilei Zhao; Qiuli Wu; Feng Chen (Journal of Zhejiang University-SCIENCE B, 2026)

Forecasting of large-scale tea anthracnose in mountainous region of China though integration of multi-source habitat information with spatiotemporal phenological corrections - Yujuan Huang; Huiqin Ma; Cong Xu; Lin Yuan; Jingfeng Huang; Zijing Jin; Jingcheng Zhang (European Journal of Agronomy, 2026)

Temporal Memory Mechanisms and Biome‐Specific Drivers of Ecosystem Carbon Flux: Insights From Explainable Deep Learning Modeling - Teng Ma; Wei He; Shuangxi Fang; Jingfeng Xiao; Ngoc Tu Nguyen; Hua Yang; Peipei Xu; Chengcheng Huang; Mengyao Zhao; Shuai Liu; Xinhui Lei; Ziyi Huang (Global Change Biology, 2026)
Ecosystem carbon dynamics are governed by complex temporal dependencies and environmental interactions, yet these processes remain poorly understood and quantified across diverse biomes. Here, we developed an explainable LSTM‐Attention framework that integrates LSTM networks, attention mechanisms, and gradient‐based attribution methods to reveal temporal dependencies in ecosystem carbon flux responses by analyzing eddy covariance flux measurements from 71 sites spanning eight North American biomes. Using this approach, we identified three distinct temporal memory patterns governing carbon flux responses. Grasslands exhibit short‐term memory dominance with exponentially increasing temporal contributions from distant to recent past. Deciduous broadleaf forests and wetlands show long‐term memory dominance, with deciduous broadleaf forests displaying the strongest historical dependence (attribution values declining from 0.30 at 6 months to 0.045 at 1 month). Croplands and evergreen needleleaf forests demonstrate U‐shaped dual memory patterns. Building on these temporal patterns, we identified biome‐specific environmental drivers operating within each memory framework: wetlands primarily controlled by soil moisture, evergreen needleleaf forests by radiation, and closed shrublands by vapor pressure deficit. Beyond individual drivers, we uncovered critical nonlinear interactions that diverged from linear correlations at most sites (55 of 71 with ρ

Electrochemically assisted activation of peroxymonosulfate by Cu-Co bimetallic carbon nitride for enhanced deoxynivalenol degradation - Bingjie Wang; Xi Zhang; Zhixia Wu; Chenyu Li; Jingfeng Wang; Xu Han (Journal of Environmental Chemical Engineering, 2025)

In-depth deciphering of partial sulfur autotrophic denitrification: Strategic S/N control and mechanistic interplay of Zn and dialkyldimethylammonium compounds on system performance and resistance genes transmission - Yukun Yuan; Jingfeng Gao; Zhiqi Wang; Yi Guo; Hongxin Xu; Liqin Zeng; Yifan Zhao (Chemical Engineering Journal, 2025)

Projecting city-scale energy performance under future weather scenarios through urban building energy modelling incorporating cluster archetypes - Jingfeng Zhou; Jiying Chen; Kaixuan Wang; Bingyu Xu; Xuhui Lin; Jiayi Yan; Meng Wang (Sustainable Cities and Society, 2025)

Preparation and characterization of glutamine/chito-oligosaccharide modified zein nanoparticles: Controlled release naringin and anti-diabetes - Yiyan Guo; Mingze Xu; Jiapeng Chen; Jingfeng Che; Wenqing Zhu; Yuxin Zheng; Wanting Huang; Wenjun Dai; Hong Chen; Limin Zhai; Li Zhang; Yan-Qing Guan (Food Chemistry, 2025)

Net ecosystem exchange of CO2 and its driving mechanisms in an island forest nature reserve in southern China - Liangxu Wu; Shuya Xie; Xianglan Li; Pengpeng Tian; Zhe Xu; Yuting Huang; Jingfeng Xiao; Xintong Chen; Minghai Xu; Wei Chen; Houcai Cai (CATENA, 2025)

Coupled retrieval of turbulent heat fluxes and gross primary productivity via the assimilation of land surface temperature data from geostationary satellites - Zongbin Xu; Tongren Xu; Xinlei He; Jingfeng Xiao; Sayed M. Bateni; Changhyun Jun; Gangqiang Zhang; Wenting Ming; Shaomin Liu (Remote Sensing of Environment, 2025)

Inconsistencies in global soil moisture products and discrepancies in their relationship with vegetation productivity - Xinyao Xu; Xufeng Wang; Jingfeng Xiao; Songlin Zhang; Yanpeng Yang; Xing Li; Te Sha; Zongxing Li (Journal of Hydrology, 2025)

Mechanical Behavior and Fracture Evolution of Non-Persistent Rock Joints Using Digital Image Correlation - Xinggang Wang; Xin Jin; Shuaishuai Wang; Jingfeng Shi; Yong Xu; Shuqi Ma; Qilin Yan (Geotechnical and Geological Engineering, 2025)

Disinfectant-driven selective gene expression and metabolic evolution: Unstable nitrite accumulation and enhanced anammox activity in mixotrophic partial denitrification/anammox system - Yi Guo; Jingfeng Gao; Yi Zhang; Tian Xie; Hongxin Xu; Yuxuan Wang (Journal of Hazardous Materials, 2025)

Responses mechanisms of resistance genes in partial nitrification and anammox system under single and combined exposure to polystyrene nanoplastics and dodecyl dimethyl benzyl ammonium chloride - Yi Zhang; Jingfeng Gao; Yi Guo; Ying Liu; Tian Xie; Hongxin Xu; Hanyi Wang (Chemical Engineering Journal, 2025)

Machine learning approaches for predicting antibiotic resistance genes abundance changes during biological nitrogen removal process - Tianyi Lu; Jingfeng Gao; Ke Zhang; Yifan Zhao; Hongxin Xu (Journal of Environmental Management, 2025)

Numerical analysis and calculation methods on the axial-loaded compressive behavior of cross-shaped partially encased concrete composite columns - Shuqing Tao; Yong Liu; Jingfeng Wang; Peng Gao; Qijun Yu; Qiuyu Xu; Jingzhe Li (Engineering Structures, 2025)

Decadal transport of trace elements in a cave system based on 16 years monitoring data: Implications for paleoclimate reconstruction - Xin Fu; Yan Yang; Jingyao Zhao; Yidong Li; Xiaomin Chen; Zhimao Ye; Mingyang Li; Jingfeng Lin; Yanzhi Xu (Applied Geochemistry, 2025)

The interaction between banana polyphenols and starch improves the bioavailability of polyphenols after non-co-heating complexation - Yajuan Qin; Jingfeng Ran; Xiaoai Chen; Xuan Zhang; Yutong Zhang; Fei Xu; Kexue Zhu; Cuiping Yi; Yanjun Zhang (Food Hydrocolloids, 2025)

Elevated dissolved oxygen alleviated the stimulation of ciprofloxacin and alkyltrimethyl ammonium compound on the dissemination of resistance genes in nitrifying system - Hongxin Xu; Jingfeng Gao; Hanyi Wang; Tianyi Lu; Ke Zhang (Chemical Engineering Journal, 2025)

Effects of combined stressors to TCDD and high temperature on HSP/CYPs signaling in the zebrafish embryos/larvae - Hongsong Chen; Hao Chen; Lian Hua; Yunqi Gao; Yuehua Yao; Yangfan Xu; Jingfeng Yang; Lingtian Xie; Yongju Luo; Ting Huang; Hongxing Chen; Xuguang Lin; et al. (Environmental Pollution, 2025)

Elucidating responses of anammox system to the single and combined short-term stress of benzethonium chloride and polyurethane microplastics: Performance, community structure and resistance genes - Tianyi Lu; Jingfeng Gao; Jingqiang Zhao; Yifan Zhao; Hongxin Xu; Yuxuan Wang; Ke Zhang (Chemical Engineering Journal, 2025)

TG-Net: A Physically Interpretable Deep Learning Forecasting Model for Thunderstorm Gusts - Yunqing Liu; Lu Yang; Mingxuan Chen; Jianwei Si; Maoyu Wang; Wenyuan Li; Jingfeng Xu (Journal of Meteorological Research, 2025)

Experimental and numerical study on the flexural performance of composite beams with channel-section steel girder under fire exposure - Yong Liu; Qiuyu Xu; Lanhui Guo; Jingfeng Wang (Engineering Structures, 2025)

An overview on the legacy and risks of Polychlorinated Biphenyls (PCBs) and Organochlorinated Pesticides (OCPs) in the polar regions - Peng Zhang; Jing Wang; Andrew Sweetman; Linke Ge; Rongguang Xing; Hao Ji; Jingfeng Yan; Qian Xiao; Yaqing Cui; Hongrui Ma; Sisi Xu (Marine Pollution Bulletin, 2024)

Evolution of microbial community and resistance genes in denitrification system under single and combined exposure to benzethonium chloride and methylparaben - Ke Zhang; Jingfeng Gao; Tianyi Lu; Yuxuan Wang; Jinming Zhang; Jiawen An; Hongxin Xu (Journal of Hazardous Materials, 2024)

Quaternary ammonium compounds inhibited phosphorus removal performance and aggravated the spread of resistance genes in enhanced biological phosphorus removal systems - Jiawen An; Jingfeng Gao; Jingqiang Zhao; Yingchao Cui; Liqin Zeng; Hongxin Xu; Qian Wang (Chemical Engineering Journal, 2024)

Spinach leaf disease identification based on deep learning techniques - Laixiang Xu; Jingfeng Su; Bei Li; Yongfeng Fan; Junmin Zhao (Plant Biotechnology Reports, 2024)

Doppler Compensation Techniques for M-Ary Sequence Spread Spectrum Signals Based on Correlation Cost Factors in Mobile Underwater Acoustic Communication - Yubo Han; Shuping Han; Heng Zhao; Yaohui Hu; Jingfeng Xu; Gang Yang (Journal of Marine Science and Engineering, 2024)
Unlike terrestrial radio, the speed of sound in the ocean is relatively slow, which results in mobile underwater M-ary spread spectrum communication typically exhibiting significant and variable multipath effects along with strong Doppler effects, leading to rapid carrier phase shifts in the received signal that severely impact decoding accuracy. This study aims to address the issue of rapid carrier phase shifts caused by significant time-varying Doppler shifts during mobile underwater M-SS communication. This paper innovatively proposes a method for updating matched filters based on correlation cost factors. By calculating the correlation cost factors for each received symbol, the method guides the direction of Doppler estimation and updates the matched filters. After identifying the optimal match, the received symbols are shifted, correlated, and decoded. Simulation and sea trial results indicate that this method demonstrates higher computational efficiency and improved decoding accuracy compared to traditional Doppler estimation matched filters under low signal-to-noise ratio conditions, and exhibits greater robustness under complex motion conditions.

Habitat quality evaluation and pattern simulation of coastal salt marsh wetlands - Yuting Huang; Guanghui Zheng; Xianglan Li; Jingfeng Xiao; Zhe Xu; Pengpeng Tian (Science of The Total Environment, 2024)

Surface iso-transformation and floatability of calcite and fluorite - Xu Yang; Yubiao Li; Jingfeng Chen; Peng Chen; Shunxin Xie; Shaoxian Song (Minerals Engineering, 2024)

Exposure to zinc and dialkyldimethyl ammonium compound alters bacterial community structure and resistance gene levels in partial sulfur autotrophic denitrification coupled with the Anammox process - Yukun Yuan; Jingfeng Gao; Zhiqi Wang; Hongxin Xu; Liqin Zeng; Xiaoyu Fu; Yifan Zhao (Journal of Hazardous Materials, 2024)

Insight into the responses of performance, bacterial community and three-fraction resistance genes to different quaternary ammonium compounds in nitrifying system under the stress of environmental ciprofloxacin - Hongxin Xu; Jingfeng Gao; Yukun Yuan; Liqin Zeng; Yuxuan Wang; Hanyi Wang; Jiawen An (Chemical Engineering Journal, 2024)

A Deep Learning Approach for Forecasting Thunderstorm Gusts in the Beijing-Tianjin-Hebei Region - Yunqing Liu; Lu Yang; Mingxuan Chen; Linye Song; Lei Han; Jingfeng Xu (Advances in Atmospheric Sciences, 2024)

The combination of ciprofloxacin and dialkyldimethyl ammonium compound synergistically proliferated intracellular resistance genes in nitrifying system - Hongxin Xu; Jingfeng Gao; Yingchao Cui; Zhiqi Wang; Yifan Zhao; Yukun Yuan; Liqin Zeng; Xiaoyu Fu (Science of The Total Environment, 2024)

Spatial heterogeneity plays a vital role in shaping the structure and function of estuarine carbon-fixing bacterial communities - Jianrong Xu; Hongxia Ming; Kaijia Ren; Dongwei Li; Huiling Huang; Jiajie Li; Kuishuang Shao; Hongjun Li; Jingfeng Fan (Marine Environmental Research, 2024)

Response of nitrification system to co-exposure of sucralose and single or combined disinfectants: Reducing damage to nitrification performance and aggravating the spread of intracellular resistance genes - Liqin Zeng; Jingfeng Gao; Yingchao Cui; Yifan Zhao; Yi Guo; Yukun Yuan; Hongxin Xu (Chemical Engineering Journal, 2024)

Optimization of the electrode reaction kinetics of V2O5 via polyacrylonitrile intercalation for high-performance magnesium batteries - Rongrui Deng; Zhongting Wang; Shuangshuang Tan; Xueting Huang; Zhipeng Gao; Yongheng Fang; Chunfeng Chen; Ronghua Wang; Chaohe Xu; Guangsheng Huang; Jingfeng Wang; Fusheng Pan (Chemical Engineering Journal, 2024)

CRISPR/Cas12b assisted loop-mediated isothermal amplification for easy, rapid and sensitive quantification of chronic HBV DNA in one-pot - Haipo Xu; Gengping Lin; Ronghua Chen; Zhixiong Cai; Yupeng Sun; Xiaolong Zhang; Bixing Zhao; Yongyi Zeng; Jingfeng Liu; Xiaolong Liu (Analytica Chimica Acta, 2024)

Mechanisms on the removal of gram-negative/positive antibiotic resistant bacteria and inhibition of horizontal gene transfer by ferrate coupled with peroxydisulfate or peroxymonosulfate - Xiaoyu Fu; Jingfeng Gao; Qian Wang; Hao Chen; Ying Liu; Liqin Zeng; Yukun Yuan; Hongxin Xu (Journal of Hazardous Materials, 2024)

Identification of acetaminophen degrading microorganisms in mixed microbial communities using 13C-DNA stable isotope probing - Yingchao Cui; Jingfeng Gao; Yongqing Gao; Fangbo Bao; Yi Guo; Liqin Zeng; Hongxin Xu; Jiawen An (Chemical Engineering Journal, 2024)

Co-exposure with cadmium elevates the toxicity of microplastics: Trojan horse effect from the perspective of intestinal barrier - Liehai Hu; Xiaoyan Feng; Yuzhi Lan; Jingfeng Zhang; Penghui Nie; Hengyi Xu (Journal of Hazardous Materials, 2024)

Plant community diversity alters the response of ecosystem multifunctionality to multiple global change factors - Zhenwei Xu; Xiao Guo; Warwick J. Allen; Xiaona Yu; Yi Hu; Jingfeng Wang; Mingyan Li; Weihua Guo (Global Change Biology, 2024)
Biodiversity is considered important to the mitigation of global change impacts on ecosystem multifunctionality in terrestrial ecosystems. However, potential mechanisms through which biodiversity maintains ecosystem multifunctionality under global change remain unclear. We grew 132 plant communities with two levels of plant diversity, crossed with treatments based on 10 global change factors (nitrogen deposition, soil salinity, drought, plant invasion, simulated grazing, oil pollution, plastics pollution, antibiotics pollution, heavy metal pollution, and pesticide pollution). All global change factors negatively impacted ecosystem multifunctionality, but negative impacts were stronger in high compared with low diversity plant communities. We explored potential mechanisms for this unexpected result, finding that the inhibition of selection effects (i.e., selection for plant species associated with high ecosystem functioning) contributed to sensitivity of ecosystem multifunctionality to global change. Specifically, global change factors decreased the abundance of novel functional plants (i.e., legumes) in high but not low diversity plant communities. The negative impacts of global change on ecosystem multifunctionality were also mediated by increased relative abundance of fungal plant pathogens (identified from metabarcoding of soil samples) and their negative relationship with the abundance of novel functional plants. Taken together, our experiment highlights the importance of protecting high diversity plant communities and legumes, and managing fungal pathogens, to the maintenance of ecosystem multifunctionality in the face of complex global change.

Different fates of extracellular and intracellular antibiotic resistance genes in flocs, granular and biofilm nitrification systems under the stress of acetaminophen - Yingchao Cui; Jingfeng Gao; Liqin Zeng; Yi Guo; Hongxin Xu; Mingyan Zhao (Journal of Hazardous Materials, 2024)

Insight into the evolution of microbial communities and resistance genes induced by sucralose in partial nitrification system with triclosan pre-exposure - Liqin Zeng; Jingfeng Gao; Yingchao Cui; Zhiqi Wang; Yifan Zhao; Yukun Yuan; Hongxin Xu; Xiaoyu Fu (Journal of Hazardous Materials, 2024)

Deciphering responses of sulfur autotrophic denitrification system to the single and joint stress of Zn(II) and dialkyldimethyl ammonium compounds: Performance, microbial community and different fractions of resistance genes - Yukun Yuan; Jingfeng Gao; Zhiqi Wang; Liqin Zeng; Hongxin Xu; Xiaoyu Fu; Yifan Zhao (Chemical Engineering Journal, 2023)

Aflatoxin B1-induced early developmental hepatotoxicity in larvae zebrafish - Chi Feng; Hongxia Bai; Xu Chang; Zhixuan Wu; Wu Dong; Qianqian Ma; Jingfeng Yang (Chemosphere, 2023)

AIEgen-based nanotherapeutic strategy for enhanced FLASH irradiation to prevent tumour recurrence and avoid severe side effects - Meng Lyu; Tianfu Zhang; Yang Li; Jingfeng Xiang; Daoming Zhu; Ligang Xia; Bin Guo; Youhua Xu; Haijun Yu; Benzhong Tang (Chemical Engineering Journal, 2023)

Axial compressive performance of partially encased steel-concrete composite stub columns filled with lightweight aggregate concrete - Zhenghao Qian; Jingfeng Wang; Yong Liu; Qiuyu Xu (Engineering Structures, 2023)

A comparative study of renewable and fossil fuels energy impacts on green development in Asian countries with divergent income inequality - Jiaqi Xu; Jingfeng Zhao; Wen Liu (Resources Policy, 2023)

Growth of grasses and forbs, nutrient concentration, and microbial activity in soil treated with microbeads - Jingfeng Wang; Xiao Guo; Janice Brahney; Zhenwei Xu; Yi Hu; Wenyi Sheng; Yanni Chen; Mingyan Li; Weihua Guo (Environmental Pollution, 2023)

BsEXLX of engineered Trichoderma reesei strain as dual-active expansin to boost cellulases secretion for synergistic enhancement of biomass enzymatic saccharification in corn and Miscanthus straws - Chengbao Xu; Tao Xia; Hao Peng; Peng Liu; Yihong Wang; Yanting Wang; Heng Kang; Jingfeng Tang; Muhammad Nauman Aftab; Liangcai Peng (Bioresource Technology, 2023)

Hotspots of riverine greenhouse gas (CH4, CO2, N2O) emissions from Qinghai Lake Basin on the northeast Tibetan Plateau - Penglin Lin; Zhiheng Du; Lei Wang; Jingfeng Liu; Qian Xu; Jia Du; Rui Jiang (Science of The Total Environment, 2023)

Cation-π interaction in Mg(OH)2@GO-coated activated carbon fiber cloth for rapid removal and recovery of divalent metal cations by flow-through adsorption - Xiao Wang; Jingfeng Li; Qiang Guo; Menglan Xu; Xiaohan Zhang; Tong Li (Resources, Conservation and Recycling, 2023)

16S Next-generation sequencing and quantitative PCR reveal the distribution of potential pathogens in the Liaohe Estuary - Huiling Huang; Shuaijun Zan; Hongxia Ming; Mengfei Li; Jianrong Xu; Yuyang Xie; Wenjing Wang; Jingfeng Fan (Frontiers in Marine Science, 2022)
The existence of potentially pathogenic bacteria seriously threatens aquatic animals and human health. Estuaries are closely related to human activities, and the detection of pathogens is important for aquaculture and public health. However, monitoring only indicator microorganisms and pathogens is not enough to accurately and comprehensively estimate water pollution. Here, the diversity of potentially pathogenic bacteria in water samples from the Liaohe estuary was profiled using 16S next-generation sequencing (16S NGS) and quantitative polymerase chain reaction (qPCR) analysis. The results showed that the dominant genera of environmental pathogens were Pseudomonas , Vibrio , Mycobacterium , Acinetobacter , Exiguobacterium , Sphingomonas , and Legionella , and the abundance of enteric pathogens was significantly less than the environmental pathogens, mainly, Citrobacter , Enterococcus , Escherichia-Shigella , Enterobacter , Bacteroides . The qPCR results showed that the 16S rRNA genes of Vibrio were the most abundant, with concentrations between 7.06 and 9.48 lg copies/L, followed by oaa gene, fliC gene, trh gene, and uidA gene, and the temperature and salinity were the main factors affecting its abundance. Variance partitioning analysis (VPA) analysis of spatial factors on the potential pathogen’s distribution (19.6% vs 5.3%) was greater than environmental factors. In addition, the co-occurrence analysis of potential pathogens in the estuary revealed significant co-occurrence among the opportunistic pathogens Testosteronemonas , Brevimonas vesicularis , and Pseudomonas putida . Our findings provide an essential reference for monitoring and occurrence of potentially pathogenic bacteria in estuaries.

A novel utilization of raw sepiolite: preparation of magnetic adsorbent directly based on sol–gel for adsorption of Pb(II) - Jiang Xu; Jingfeng He; Lingtao Zhu; Shulian Guo; Hao Chen (Environmental Science and Pollution Research, 2022)

Pseudoephedrine hydrochloride causes hyperactivity in zebrafish via modulation of the serotonin pathway - Yini Zhou; Tonglaga Li; Shangzi Zhou; Han Xu; Xiaoyu Yin; Hao Chen; Xuan Ni; Meirong Bai; Wuliji Ao; Jingfeng Yang; R. G. Ahmed; Xuefu Zhang; et al. (Metabolic Brain Disease, 2022)

Potato (Solanum tuberosum L.) non-specific lipid transfer protein StLTP6 promotes viral infection by inhibiting virus-induced RNA silencing - Kaijie Shang; Yang Xu; Weilin Cao; Xiaoying Xie; Yanru Zhang; Jingfeng Zhang; Hongmei Liu; Shumei Zhou; Xiaoping Zhu; Changxiang Zhu (Planta, 2022)

Canopy photosynthetic capacity drives contrasting age dynamics of resource use efficiencies between mature temperate evergreen and deciduous forests - Hang Xu; Jingfeng Xiao; Zhiqiang Zhang; Scott V. Ollinger; David Y. Hollinger; Yude Pan; Jiaming Wan (Global Change Biology, 2020)
Forest resource use efficiencies (RUEs) can vary with tree age, but the nature of these trends and their underlying mechanisms are not well understood. Understanding the age dynamics of forest RUEs and their drivers is vital for assessing the trade‐offs between forest functions and resource consumption, making rational management policy, and projecting ecosystem carbon dynamics. Here we used the FLUXNET2015 and AmeriFlux datasets and published literature to explore the age‐dependent variability of forest light use efficiency (LUE) and inherent water use efficiency as well as their main regulatory variables in temperate regions. Our results showed that evergreen forest RUEs initially increased before reaching the mature stage (i.e., around 90 years old), and then gradually declined; in contrast, RUEs continuously increased with age for mature deciduous forests. Changing canopy photosynthetic capacity ( A max ) was the primary cause of age‐related changes in RUEs across temperate forest sites. More importantly, soil nitrogen (N) increased in mature deciduous forests through time but decreased in older evergreen forests. The age‐dependent changes in soil N were closely linked with the age dynamics of A max for mature temperate forests. Additionally, soil nutrient conditions played a greater role in deciduous forest RUEs than evergreen forest RUEs. This study highlights the importance of stand age and forest type on temperate forest RUEs over the long term.

A deep learning approach to conflating heterogeneous geospatial data for corn yield estimation: A case study of the US Corn Belt at the county level - Hao Jiang; Hao Hu; Renhai Zhong; Jinfan Xu; Jialu Xu; Jingfeng Huang; Shaowen Wang; Yibin Ying; Tao Lin (Global Change Biology, 2020)
Understanding large‐scale crop growth and its responses to climate change are critical for yield estimation and prediction, especially under the increased frequency of extreme climate and weather events. County‐level corn phenology varies spatially and interannually across the Corn Belt in the United States, where precipitation and heat stress presents a temporal pattern among growth phases (GPs) and vary interannually. In this study, we developed a long short‐term memory (LSTM) model that integrates heterogeneous crop phenology, meteorology, and remote sensing data to estimate county‐level corn yields. By conflating heterogeneous phenology‐based remote sensing and meteorological indices, the LSTM model accounted for 76% of yield variations across the Corn Belt, improved from 39% of yield variations explained by phenology‐based meteorological indices alone. The LSTM model outperformed least absolute shrinkage and selection operator (LASSO) regression and random forest (RF) approaches for end‐of‐the‐season yield estimation, as a result of its recurrent neural network structure that can incorporate cumulative and nonlinear relationships between corn yield and environmental factors. The results showed that the period from silking to dough was most critical for crop yield estimation. The LSTM model presented a robust yield estimation under extreme weather events in 2012, which reduced the root‐mean‐square error to 1.47 Mg/ha from 1.93 Mg/ha for LASSO and 2.43 Mg/ha for RF. The LSTM model has the capability to learn general patterns from high‐dimensional (spectral, spatial, and temporal) input features to achieve a robust county‐level crop yield estimation. This deep learning approach holds great promise for better understanding the global condition of crop growth based on publicly available remote sensing and meteorological data.

Spatial econometric analysis of carbon emission intensity in Chinese provinces from the perspective of innovation-driven - Song Liang; Jingfeng Zhao; Shumin He; Qingqing Xu; Xin Ma (Environmental Science and Pollution Research, 2019)

Malnutrition worsens fluorosis-induced damage in hypothalamic-pituitary-ovarian axis of rats - Yongmei Liu; Ling Li; Jingfeng Xu; Siwen Yu; Shijun Wang; Maojuan Yu; Wenbing Zou; Mingliang Cheng; Shuhua Xia (Molecular & Cellular Toxicology, 2019)

Enrichment, Distribution of Vanadium-Containing Protein in Vanadium-Enriched Sea Cucumber Apostichopus japonicus and the Ameliorative Effect on Insulin Resistance - Yanjun Liu; Qingxin Zhou; Yanlei Zhao; Yiming Wang; Yuming Wang; Jingfeng Wang; Jie Xu; Changhu Xue (Biological Trace Element Research, 2016)

Assessment of total and organic vanadium levels and their bioaccumulation in edible sea cucumbers: tissues distribution, inter-species-specific, locational differences and seasonal variations - Yanjun Liu; Qingxin Zhou; Jie Xu; Yong Xue; Xiaofang Liu; Jingfeng Wang; Changhu Xue (Environmental Geochemistry and Health, 2016)

Green Synthesis of Oxovanadium(IV)/chitosan Nanocomposites and Its Ameliorative Effect on Hyperglycemia, Insulin Resistance, and Oxidative Stress - Yanjun Liu; Xu Jie; Yongli Guo; Xin Zhang; Jingfeng Wang; Changhu Xue (Biological Trace Element Research, 2016)

Trends in the daily and extreme temperatures in the Qiantang River basin, China - Fang Xia; Xingmei Liu; Jianming Xu; Zhonggen Wang; Jingfeng Huang; Philip C. Brookes (International Journal of Climatology, 2015)
Temporal and spatial changes in the annual and seasonal temperatures in a typical basin of the Qiantang River were analysed based on the time series databases of daily temperatures from 14 meteorological stations. Both the Mann–Kendall ( MK ) trend test and simple linear regression analyses were employed to detect trends in the mean and extreme temperatures. The temperature changes during the three periods of 1960–1990, 1960–2000 and 1960–2006 were investigated at each meteorological station and over the entire basin as an average. The spatial and temporal changes were characterized by significant warming throughout the region, with the minimum temperature (Tn) increasing the most, particularly after 1990. Various percentiles of extreme temperatures, as well as their corresponding frequencies, were chosen to explore the trends of extreme climate change in this region. Linear regression analyses showed a significant warming trend in cold events both on an annual and seasonal basis, especially in the winter. Conversely, the hot events were dominated by an insignificant warming trend ( p > 0.05). When comparing the time series before and after 1990, trend shifts were apparent in both the mean and extreme temperatures, particularly in the spring and winter. In addition to the large‐scale circulation, regional factors may have influenced the observed climate change in the studied region. Climate change has already influenced human society by, for example, increasing the frequency of haze in the study region. We conclude that the warming here is mainly attributed to changes in the minimum temperature.

Effects of dietary sea cucumber saponin on the gene expression rhythm involved in circadian clock and lipid metabolism in mice during nighttime-feeding - Min Wen; Jie Cui; Jie Xu; Yong Xue; Jingfeng Wang; Changhu Xue; Yuming Wang (Journal of Physiology and Biochemistry, 2014)

Etiology and epidemiology of viral diarrhea in children under the age of five hospitalized in Tianjin, China - Yabo Ouyang; Hui Ma; Min Jin; Xinwei Wang; Jingfeng Wang; Lu Xu; Shuxiang Lin; Zhiqiang Shen; Zhaoli Chen; Zhigang Qiu; Zhixian Gao; Lin Peng; et al. (Archives of Virology, 2012)